Noise Study of Small Ships during Sailing in Near-wake Field based on Body Force Model. Issue 1 (July 2021) - He, Xiaohui; Liu, Zhongle; Yuan, Zhiyong; Ruan, Yingying
Abstract: Noises of ships during sailing and in the near-wake field are both important factors in the ship design, which is of great significance to the ship structure and personnel health. A convenient body force model is adopted to replace the action of a real propeller through the computational fluid dynamics (CFD) method, meanwhile, FW-H equation is used to calculate the radiated noise in the near-wake field of small ships and forecast the noise characteristics of small ships during sailing in the near-wake field. The variation law of noise spectrum at different monitoring points during the evolution of the near-wake field is analyzed, and the simulating results are in good agreement with the testing data. Research proves that the body force model is efficient and feasible to the noise characteristics of small ships during sailing in the near-wake field, which can provide some reference for the design of small ships and also for the noise prediction in the near-wake field.